2006
DOI: 10.1111/j.1470-6431.2006.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological consumer behaviour: an empirical analysis

Abstract: Increasingly, consumers choose ecological products when they do the shopping, not only because it is a healthier option but also because it helps to sustain the environment for future generations. They are prepared to switch products for ecological reasons and stop buying products from companies that cause pollution. Firms and other economic institutions are aware of the importance of reflecting these attitudes towards the environment in developing their products. This paper is focused on environmental attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
169
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(201 citation statements)
references
References 34 publications
9
169
1
6
Order By: Relevance
“…The findings of the studies of Roubanis [33], Isaka [27] and Fogarty's [74] support the hypothesis that a high level of VSL is very rare in college-age students. In an investigation comparing environmentally-responsible consumerism (ERC) and the voluntary simplicity lifestyle (VSL), between Meredith College students in the USA [33] and Japanese female college students in Osaka Shoin Women's University (Osaka, Japan) [32], it was shown that both groups of respondents were striving to meet their needs of self-esteem and efficacy through their consumption behaviors.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The findings of the studies of Roubanis [33], Isaka [27] and Fogarty's [74] support the hypothesis that a high level of VSL is very rare in college-age students. In an investigation comparing environmentally-responsible consumerism (ERC) and the voluntary simplicity lifestyle (VSL), between Meredith College students in the USA [33] and Japanese female college students in Osaka Shoin Women's University (Osaka, Japan) [32], it was shown that both groups of respondents were striving to meet their needs of self-esteem and efficacy through their consumption behaviors.…”
Section: Discussionsupporting
confidence: 70%
“…Compared to other studies in this area, the results differ according to age, level of education and material status. As a whole, VS are identified as middle-aged people, well educated (more highly educated than the general population) and financially secure (household income over the national average), inter alia [23,27,33,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that personality variables were better predictors than the socioeconomic variables. Other scholars found individual personal attitudes and beliefs to be significant in predicting green behavior (in term of their purchases) (Gan et al 2008;Fraj and Martinez 2007a;Chan, 2001). Other than environmental knowledge, attitudes and values of individuals have been found to be major factors that influence green competencies (Ramayah, Lee, and Mohamad, 2010;Zho et al, 2014).…”
Section: Green Human Resource Management and Green Competenciesmentioning
confidence: 99%
“…This explains why, for example, consumers who express concerns for the environment may not engage in the actual green purchase behavior (Laroche et al 2002;Fraj and Martinez 2007a;Tan and Lau 2010;Tan and Lau 2011). As a result, we divide green attitudes into general (i.e., green purchase intention (GPI) and specific, (i.e., green purchase attitude (GPA)), and explore their relationships with green competencies respectively.…”
Section: Acquired Green Competenciesmentioning
confidence: 99%